Assessing the Impact of Nutritional Interventions for Pregnant Women and Malnourished Children in Nigerian IDP Camps - Babajide Victor Bello; Juliana Agmada Shaba (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Internally displaced persons (IDPs) in Nigeria face severe nutritional challenges, with pregnant women and children particularly vulnerable to malnutrition and its associated health risks. This study evaluates the effectiveness and impact of targeted nutritional interventions implemented in IDP camps across Nigeria, focusing on both immediate health outcomes and longer-term developmental indicators. Using a multidisciplinary assessment framework, the study examines comprehensive interventions designed to address maternal and child malnutrition within the context of a protracted displacement crisis. The results demonstrate significant improvements in maternal and child health outcomes following the implementation of nutrition-specific programs. However, persistent barriers, such as supply chain disruptions, cultural resistance, and inadequate sanitation infrastructure—continue to hinder program sustainability and reach. These findings highlight the need for sustained, multi-sectoral strategies that integrate nutritional support with broader health system strengthening, improved camp infrastructure, and culturally sensitive programming. The study offers critical insights for policymakers, humanitarian actors, and health practitioners seeking to enhance food security and resilience among displaced populations in Nigeria.